2018
DOI: 10.1038/s41598-018-25439-z
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Fibroblast Growth Factor-23 Levels are Associated with an Increased Risk of Anemia Development in Patients with Nondialysis Chronic Kidney Disease

Abstract: Fibroblast growth factor-23 (FGF23) is an established biomarker of adverse outcomes in patients with chronic kidney disease (CKD). Several cross-sectional studies have suggested a possible association between FGF23 and anemia in these patients. In this large-scale prospective cohort study, we investigated this relationship and examined whether high FGF23 levels increase the risk of incident anemia. This prospective longitudinal study included 2,089 patients from the KoreaN cohort study for Outcome in patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 43 publications
4
33
1
Order By: Relevance
“…This finding, which has not been previously reported in CKD stage 1-5 patients, is in accordance with studies in hemodialysis and transplanted patients, in whom the presence of iron deficiency promoted a rise in FGF-23 levels and on the contrary, iron intravenous administration reduced its levels [43,44]. Of note, a recent paper, again in non dialysis CKD patients, found that high serum FGF-23 levels were associated with an increased risk for anemia [45]. Finally, serum levels of 25-OH vitamin D were significantly higher in the group of patients with lower than median cFGF-23 value and also lower than median value of serum phosphate.…”
Section: Cfgf-23 and Sklotho Associations With Cardiovascular Risk Fasupporting
confidence: 91%
“…This finding, which has not been previously reported in CKD stage 1-5 patients, is in accordance with studies in hemodialysis and transplanted patients, in whom the presence of iron deficiency promoted a rise in FGF-23 levels and on the contrary, iron intravenous administration reduced its levels [43,44]. Of note, a recent paper, again in non dialysis CKD patients, found that high serum FGF-23 levels were associated with an increased risk for anemia [45]. Finally, serum levels of 25-OH vitamin D were significantly higher in the group of patients with lower than median cFGF-23 value and also lower than median value of serum phosphate.…”
Section: Cfgf-23 and Sklotho Associations With Cardiovascular Risk Fasupporting
confidence: 91%
“…In CKD patients, associations of FGF23 serum concentrations with hemoglobin levels and the presence of anemia have been described [ 17 , 18 , 19 ]. However, in these studies, only cFGF23 was measured and no analysis of potential underlying mechanisms was undertaken.…”
Section: Introductionmentioning
confidence: 99%
“…In a cross-sectional study of patients representing a spectrum of CKD severity, increased FGF23 levels were significantly associated with deteriorating renal function [ 15 ]. For reasons that are not yet clear, FGF23 also may be related to the development of iron deficiency anemia; in a recent cohort study, elevated concentrations of FGF23 were associated with a higher incidence of anemia, particularly in patients with iron deficiency [ 16 ]. Importantly, increased serum FGF23 concentrations are associated with increased risk of cardiovascular events and death in CKD [ 12 ].…”
Section: Introductionmentioning
confidence: 99%